Was ist Klima? - Kraus, Helmut (ERDKUNDE, 1984)
Climatology is not a science in its own right, it is only a special way of considering the state, changes and processes in the atmosphere, i.e. in the science of meteorology and thus also of physical geography. The special way relates to the time-scale of consideration, which has to be chosen relatively large. This paper presents a climate definition based upon time- and space scales and discusses the problem of general acceptance. Within the space scale considerations,climates caused by specific surface structures (e.g. valleys, coastlines) are treated. They will be called Specific Surfaces Climates (= SSCs). This term may be useful especially in those fields, in which landforms and/or surface characteristics play an important role.